2015
DOI: 10.1136/vr.102638
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of iridociliary epithelial tumour biopsies in dogs: a retrospective study

Abstract: To evaluate the outcome of eyes with a confirmed iridociliary epithelial tumour (ICET) following biopsy. Forty-two specimens were selected from the Comparative Ocular Pathology Laboratory of Wisconsin database, including 11 globes enucleated following ICET biopsy and 31 iridociliary biopsies with a confirmed ICET. Histopathology was performed for all specimens. When identified, the corneal surgical wound was examined in enucleated globes. Tumour type and margins were determined for biopsy specimens and follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Iridociliary tumors display significant variability in pigment content and the number of mitotic figures, so degree of malignancy is assessed based on scleral invasiveness . Metastatic potential of iridociliary tumors is generally considered to be low for both adenomas and adenocarcinomas.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Iridociliary tumors display significant variability in pigment content and the number of mitotic figures, so degree of malignancy is assessed based on scleral invasiveness . Metastatic potential of iridociliary tumors is generally considered to be low for both adenomas and adenocarcinomas.…”
Section: Discussionmentioning
confidence: 88%
“…Metastatic potential of iridociliary tumors is generally considered to be low for both adenomas and adenocarcinomas. There are three cases of confirmed metastasis in the veterinary literature and three other cases of dogs with confirmed iridociliary tumors that later developed evidence of neoplasia in other parts of the body that were not histologically confirmed to represent metastasis . To the authors’ knowledge, there have been no other reported cases of bilateral iridociliary carcinoma, and it is unclear in Case 1 if the two lesions evolved separately or if one represented metastasis of the other.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Distant metastases of iridociliary carcinomas are extremely rare . The prognosis for survival in dogs and cats with ciliary body adenomas and adenocarcinomas is good, although the prognosis for the globe retention is poor as enucleation is required in most cases …”
Section: Discussionmentioning
confidence: 99%